Metodologia de Avaliação do desempenho energético da integração de carros elétricos à edificações - SOUZA, Ana Carolina Dias Barreto de (Universidade Federal do Pará, 2025)
Energy diagnosis methodologies have been incorporating energy consumption and energy generation systems into their analysis, making it possible to classify energy-self-sufficient buildings as Near Zero Energy Buildings (NZEB) or Positive Energy Buildings (PEB). In electric mobility, the increased use of electric vehicles (EVs) brings challenges and opportunities in electricity consumption, management and efficiency. The impact of this robust and growing load when integrated into new and existing buildings is not yet considered in performance assessments. Consequently, the methodologies for obtaining certifications and labels do not consider the load of this system as an individual end-use. For buildings with energy efficiency (EE) and self-sufficiency labels, introducing EVs can result in the rating being downgraded due to increased energy consumption. Therefore, analyzing the impact of integrating EVs into buildings aims to support the formulation or revision of energy diagnosis methodologies that include EV charging systems integrated into buildings. This thesis evaluates the influence of EV charging in buildings with the NZEB/PEB label from the Brazilian Building Labeling Program (PBE Edifica). Using on-site surveys, computer modelling and thermo energetic analysis with software such as OpenStudio and EnergyPlus, an energy rating was carried out on a building in Belém, State of Pará, Brazil. Subsequently, energy flow simulations using probabilistic models with the Monte Carlo method were run in OpenDSS software to examine the impact of integrating EVs without (scenario 01) and with (scenario 02) the implementation of demand-side management techniques. Analysis using the labelling methodology showed that the building has an EE level C rating and NZEB self-sufficiency. Scenario 01 generated a 69.28% increase in energy consumption, reducing the EE level to D and resulting in the loss of the NZEB class. Scenario 02 increased consumption by 40.50%, a lower percentage than scenario 01 and guaranteed the return of the NZEB class lost in scenario 1, but did not return the EE level to class C. The results highlight the need for immediate and comprehensive energy management strategies. However, these strategies are not sufficient if other consumption restrictions or EE measures are not applied to other systems in the building. To this end, EE measures were proposed and evaluated in the air conditioning and lighting systems. Subsequently, an equation was drawn up to indicate the maximum level of energy X consumption that could be increased without compromising the building's energy performance and NZEB rating. Finally, OpenDSS software was used to simulate the increased availability of EV charging after the retrofit. With the proposed retrofit, the building improved its EE ratings by three levels, and the NZEB rating percentage increased by 33.28%. These measures also increased the EV charging load by 20% while maintaining the maximum EE level and NZEB rating.